(untitled) (New York, 2004)
Mallor, Barnes, Bowers and Langvardt's, Business Law: The Ethical, Global, and E-Commerce Environment, 12th Edition, is appropriate for the two-term business law course. The cases in the 12th edition are excerpted and edited by the authors. The syntax is not altered, therefore retaining the language of the courts. As in the 11th edition, the 12th edition includes a mix of actual AND hypothetical cases. The title has been changed to reflect a new focus of the book – the global and Internet environment. Business Law: The Ethical, Global, and E-Commerce Environment, 12e includes new pedagogy such as opening vignettes and new-boxed features such as Ethics in Action and Cyberlaw in Action. This combined with case briefs and concept reviews, along with some reorganization of the text results in a more complete, relevant and user-friendly text.
Keywords: Commercial law